Remigration in Lithuania in the 21st Century: Readiness of the Education System to Accept Students from Returning Families - Bagdonaitė, Jurgita (Vilnius University Open Series, 2020)
The article analyses the readiness of the Lithuanian education system to accept children from returning families. Moreover, it determines the problems and describes the factors hindering the effective integration of remigrant children. The summarised scientific literature is illustrated by empirical research data. Based on the aforementioned data of this study, it is concluded that the concept of education of remigrant children is ever-changing. The main obstacles that Lithuanian educational institutions are facing at the moment are Lithuanian language education and nurturing, a lack of tolerance and competencies of educators. The development and creation of a cooperative environment within the school is determined to be one of the most successful methods to facilitate the job of educators.
Keywords: remigration,; children; Lituanistic schools; integration; readiness of the educational syst